Race-neutral alternatives in postsecondary education innovative approaches to diversity. - United States. Department of Education. Office for Civil Rights ([Washington, D.C.] : U.S. Dept. of Education, Office for Civil Rights, 2003)
Describes innovative "race-neutral" programs being implemented across the country.
Title from title screen (viewed on Nov. 3, 2003).
"March 2003."
Includes bibliographical references.
Text (HTML), image (GIF)
Also published in print format.
Mode of access: Internet from the DOE web site. Address as of 11/3/03: http://www.ed.gov/about/offices/list/ocr/edlite-raceneutralreport.html; current access available via PURL.
Keywords: Minorities -- Education (Higher) -- United States; Educational equalization -- United States; Multicultural education -- United States; Affirmative action programs -- United States